Incidence of venous thromboembolism among patients who underwent major surgery in a public hospital in Singapore (Medical Journal of Indonesia, 2014)
Background: Venous thromboembolism (VTE) is a fatal yet potentially preventable complication of surgery. Routine thromboprophylaxis is still unequivocal prescription is problematic due to perception of low VTE incidence among Asian population. This study aims to investigate the incidence of VTE and thromboprophylaxis prescription among patients undergoing major surgery in a Singapore hospital.Methods: This was a cross-sectional study. Data were obtained from medical record of 1,103 patients who had underwent major orthopaedic or abdominal surgery in 2011-2012 at Khoo Teck Puat Hospital, Singapore. Incidence of VTE events either in the same admission or re-admission in less than one month time were noted as study parameters.Results: Incidence of VTE was 2.1% (95% CI: 1.67 - 2.53) of which 1.3% and 0.8% were DVT and PE cases respectively. Age, gender, history of VTE, ischemic heart disease, and mechanical prophylaxis were associated with VTE incidence based on bivariate analysis. The prescription of pharmacological thromboprophylaxis was associated with prior anticoagulant medication, type of surgery, and incidence of new bleeding. Conclusion: Subsequent to major surgeries, VTE is as common in Asian patients as published data in other populations. Pharmacologic thromboprophylaxis should be considered as recommended in non-Asian guidelines.Keywords: thromboprophylaxis, venous thromboembolism